University experiences of students and graduates with neurodiversity: tools for creating a specialized mentoring program related to working life - Aguilera Rodríguez, Gerardo; Márquez González, Claudia Verónica; Villaseñor-Cabrera, Teresita J.; Valadez Sierra, María de los Dolores (Frontiers in Education, 2024)
The term neurodiversity groups a series of conditions among which are Autism, Attention Deficit and Hyperactivity Disorder, Dyslexia and Dyscalculia, in higher education is evident the presence of students who have any of these conditions, a situation that represents in most cases a barrier to their optimal academic performance according to the needs and institutional requirements and that will also have negative repercussions when trying to join the workforce. In this sense it is necessary to design strategies that allow and ensure the specialized accompaniment for this population from knowing the opinion of students in condition of neurodiversity, for that reason the objective of this work was to know the needs, difficulties and tools related to the incorporation to the working life, referred by students and graduates of the bachelor's degree in psychology who present some condition of neurodiversity. For this purpose, a qualitative/phenomenological research was carried out. From the opinions gathered, it was identified that the main needs of students are: greater awareness and capacity on the part of higher education institutions to make a timely diagnosis, make reasonable adjustments for greater and better integration in their activities, provide favorable environments, generate strategies to enhance or improve some cognitive and emotional aspects, for example: planning skills, time organization, emotional regulation skills. The results of the present research are consistent with other studies that emphasize the importance of generating a compassionate pedagogy in educational spaces, that is, a greater commitment on the part of the actors involved in education, to address and improve pedagogical practice, provide tools and generate strategies to help students who present some condition of neurodiversity throughout their careers. Limitations: The sample size, as well as the depth of the interviews, is limited; therefore, it is suggested for future research to increase the number of participants and to go deeper into the interviews.